Enzymes of glycerol-3-phosphate pathway in triacylglycerol synthesis in plants: Function, biotechnological application and evolution. (January 2019) - Maraschin, Felipe dos Santos; Kulcheski, Franceli Rodrigues; Segatto, Ana Lucia Anversa; Trenz, Thomaz Stumpf; Barrientos-Diaz, Ossman; Margis-Pinheiro, Marcia; Margis, Rogerio; Turchetto-Zolet, Andreia Carina
Abstract: Triacylglycerols (TAG) are the major form of energy storage in plants. TAG are primarily stored in seeds and fruits, but vegetative tissues also possess a high capacity for their synthesis and storage. These storage lipids are essential to plant development, being used in seedling growth during germination, pollen development, and sexual reproduction, for example. TAG are also an important source of edible oils for animal and human consumption, and are used for fuel and industrial feedstocks. The canonical pathway leading to TAG synthesis is the glycerol-3-phosphate, or Kennedy, pathway, which is an evolutionarily conserved process in most living organisms. The enzymatic machinery for synthesizing TAG is well known in several plant species, and the genes encoding these enzymes have been the focus of many studies. Here, we review recent progress on the understanding of evolutionary, functional and biotechnological aspects of the glycerol-3-phosphate pathway enzymes that produce TAG. We discuss current knowledge about their functional aspects, and summarize valuable insights into genetically engineered plants for enhancing TAG accumulation. Also, we highlight the evolutionary history of these genes and present a meta-analysis linking positive selection to gene family and plant diversification, and also to the domestication processes in oilseed crops.